Identification of Cryptosporidium. Sp and Blastocystis. Sp - Yanti Rahayu; Rauza Sukma Rita; Ilmiawati Ilmiawati; Nuzulia Irawati (Indonesian Journal of Global Health Research, 2025)
Intestinal protozoan infection is still a major health problem in children, because children are most often in contact with soil as a source of infection and are a significant threat, but are often overlooked to public health until severe or chronic complications because many of them are usually asymptomatic or only manifest mild symptoms. The purpose of this study was to determine the incidence of Cryptosporidium sp, Blastocystis sp infections in school children in Pasir Sebelah, Padang City. This type of research is descriptive categorical, the sample is primary data with a sample size of 66 children using consecutive sampling techniques. Data were collected through direct interviews with caregivers and anthropometric measurements conducted by trained enumerators using standardized tools. This study was analyzed univariately and presented in the form of a frequency distribution table. This study obtained the results of intestinal protozoan infections in children found Cryptosporidium sp 42.4% added and Blastocyctis sp 31.8%. Intestinal protozoan infections were higher in the 7-10 year age group 51.5% and higher in girls 54.5%. The conclusion of this study was that the incidence of intestinal protozoan infections was quite high in children at Elementary School 23 Padang City. Conclusions: these children need special attention, and immediate treatment for infected children and counseling on education and prevention of diseases caused by intestinal protozoa.